(untitled) (Journal of actual problems of jurisprudence, 2016)
In article advocateship is a voluntary professional organization of the citizens who are carrying out protection on pretrial investigation, inquiry, in criminal court judge in an order established by law, besides, carrying out representation of interests of claimants and respondents in civil cases were given.Advocateship is a public self-coping organization urged to provide a legal assistance to the population and organizations by consultation on legal questions, any drawing up documents and official papers on the basis of law. Мақалада адвокаттық қызметтің коптеген қырлары мен мәселелері қарастырылған және адвокаттың қылмыстық істер, азаматтық істер мен әкімшілік істерде қорғаушы болуы туралы оқыс ой-түйіндер жазылған. Адвокаттың мәртебі мен оның құқықтық мәртебесініңсауалдары зерттелген. Адвокат өзін-өзі басқара алатын қоғамдық ұйым болып табылады және адвокаттар заңға сүйене отырып, қоғамға кеңесін береді.